2022
DOI: 10.1111/cpr.13353
|View full text |Cite
|
Sign up to set email alerts
|

Adverse PFAS effects on mouse oocyte in vitro maturation are associated with carbon‐chain length and inclusion of a sulfonate group

Abstract: Objectives: Per-and polyfluoroalkyl substances (PFAS) are man-made chemicals that are widely used in various products. PFAS are characterized by their fluorinated carbon chains that make them hard to degrade and bioaccumulate in human and animals. Toxicological studies have shown PFAS toxic effects: cytotoxicity, immunotoxicity, neurotoxicity, and reproductive toxicity. However, it is still unclear how the structures of PFAS, such as carbon-chain length and functional groups, determine their reproductive toxic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 88 publications
0
21
0
Order By: Relevance
“…These results indicate that the length of the carbon chain may correlate with the level of observed toxicity, as all three compounds had the same carboxylic acid functional group and only differed by the number of carbons in their backbone. A trend of increased PFAS toxicity has been observed with increased carbon chain length and the presence of a sulfonate group [ 30 , 35 , 57 ], but to our knowledge, this is the first study which provides evidence of increased antagonistic effects of carboxylic acids with increasing carbon chain lengths co-treated with PFOS. In a similar study using zebrafish ( Danio rerio ) embryos, Ding et al [ 32 ] observed a complex interactive effect of a PFOS-PFOA mixture, observing antagonistic, additive, and synergistic effects depending on the concentration of each compound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that the length of the carbon chain may correlate with the level of observed toxicity, as all three compounds had the same carboxylic acid functional group and only differed by the number of carbons in their backbone. A trend of increased PFAS toxicity has been observed with increased carbon chain length and the presence of a sulfonate group [ 30 , 35 , 57 ], but to our knowledge, this is the first study which provides evidence of increased antagonistic effects of carboxylic acids with increasing carbon chain lengths co-treated with PFOS. In a similar study using zebrafish ( Danio rerio ) embryos, Ding et al [ 32 ] observed a complex interactive effect of a PFOS-PFOA mixture, observing antagonistic, additive, and synergistic effects depending on the concentration of each compound.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown if this is due to differences in life stages, if the mechanisms are species-specific, or a different reason. While PFOS and other sulfonic acid-containing PFAS have been attributed as major contributors to PFAS-induced oxidative stress [ 29 , 30 , 78 ], both PFOS and PFOA have been shown to up- or downregulate several oxidative stress genes in myriad fish species (summarized in Lee et al [ 7 ]). An ROS-generating mechanism of PFOS has been explored in zebrafish (Shi and Zhou [ 28 ]), but there are few comparisons between other individual PFAS and mixtures, warranting further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, longer-chain compounds with 7–10 carbons were found to be more likely to induce changes in gene expression . Prior studies, utilizing a mouse-oocyte-in vitro-maturation system to detect the toxicity of PFOA, PFHxA, PFBA, PFOS, PFHxS, and PFBS, found that the toxicity of the two major categories of PFAS, perfluoroalkyl carboxylic acid (PFCA) and perfluoroalkyl sulfonic acid (PFSA), increases with increasing carbon chain length and the inclusion of the sulfonate group . Our cytotoxicity result of evaluated PFAS aligns with this trend, with PFOS exhibiting the strongest cytotoxicity, followed by PFOA, PFHxS, PFHxA, and then PFBS and PFBA.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental exposure has led to high concentrations found in the blood and lungs due to their amphiphilic properties and high affinity for proteins such as albumin [ 1 , 2 , 19 ]. PFAS can pass through the blood ovarian follicle barrier and have been detected in follicular fluid, impacting female reproduction [ 14 , 20 , 21 , 22 , 23 ]. Other notable concentrations have been found in serum, seminal fluid, thyroid, reproductive organs, brain, and many fetal-dependent structures, such as the umbilical cord and breast milk [ 3 , 17 ].…”
Section: Introductionmentioning
confidence: 99%